Agricultural Land Capability at Teras Sub-District, Boyolali, Central Java - Sugiharto Budi Santoso; Taryono Taryono (Forum Geografi, 1999)
There are three aims on this research: to determine  about the level of farming land capability and the sub class of farming land capability, to determine the area that posible to developed for farming land, to evaluate about farming land capability for landuse in the sub district of Boyolali Regency. The methods used in this research is observation in the field and laboratory with land unit approach as a standard  of mapping. The data collected from this research is degree of slope, erosion sensibility, erosion level, solum, texture, permeability, drainage, gravel/ pebble, and the flood hazard. The result of this research showed that the research area has II to VI land capability. Land capability II: 750 Ha (25,1%), III: 1308,1 Ha (43,7%), IV: 250 Ha (8,3%), V: 386,5 Ha (13%), VI: 299 Ha (10%). The dominant restriction is the soil moisture that consist of permeability and drainage.